2018
DOI: 10.1136/rmdopen-2017-000584
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic and pharmacokinetic effects and safety of verinurad in combination with allopurinol in adults with gout: a phase IIa, open-label study

Abstract: ObjectivesVerinurad (RDEA3170) is a high affinity, selective uric acid transporter (URAT1) inhibitor indevelopment for treating gout and asymptomatic hyperuricaemia. This phase IIa study evaluated the pharmacodynamics, pharmacokinetics and safety of verinurad combined with allopurinol versus allopurinol alone in adults with gout.MethodsForty-one subjects were randomised into two cohorts of verinurad (2.5–20 mg) plus allopurinol (300 mg once daily) versus allopurinol 300 mg once daily, 600 mg once daily or 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 39 publications
6
21
0
3
Order By: Relevance
“…The results of this trial further the concept that potent URAT1 inhibitors without prolonged activities in humans, such as lesinurad and verinurad, must be given with an XOI that simultaneously reduces the production of uric acid. To this end, no subjects in the trials where verinurad was combined with an XOI have shown increases in sCr !1.5 Â baseline [24][25][26]. These results are consistent with those of lesinurad, which is associated with significant increases in renal AEs when given as monotherapy [10].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The results of this trial further the concept that potent URAT1 inhibitors without prolonged activities in humans, such as lesinurad and verinurad, must be given with an XOI that simultaneously reduces the production of uric acid. To this end, no subjects in the trials where verinurad was combined with an XOI have shown increases in sCr !1.5 Â baseline [24][25][26]. These results are consistent with those of lesinurad, which is associated with significant increases in renal AEs when given as monotherapy [10].…”
Section: Discussionsupporting
confidence: 80%
“…However, the possibility that excessive uric acid excretion is associated with nephropathy may mean that verinurad should be administered with an agent that reduces uric acid production and minimizes uric acid in the kidney. The combination of verinurad with an XOI has been successfully studied elsewhere [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that combining two treatments with different mechanisms of action can reduce sUA levels more consistently and lead to higher target achievement rates than a single agent alone at higher doses. Two other phase 2a studies investigating verinurad in combination with febuxostat or allopurinol, which were performed in Caucasian subjects with gout, also reported superior sUA lowering for the combination versus XOI treatment alone [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, a single dose of verinurad 40 mg has demonstrated to lower SUA by up to 62% whereas multiple doses of verinurad 10 mg have reached a reduction in SUA levels approximately of 61%, being well tolerated at all doses and with no serious adverse events nor significant laboratory or ECG abnormalities reported [ 94 ]. Moreover, in coadministration with allopurinol 300 mg, verinurad (2.5–20 mg) has been shown to produce a dose-dependent decrease in SUA, with no instances of serum creatinine elevation [ 95 ].…”
Section: Drugs That Inhibit the Reabsorption Of Uric Acid: The Urimentioning
confidence: 99%